Proceedings 2nd European Workshop on Usable Security 2017
DOI: 10.14722/eurousec.2017.23010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of information security risk visualization on managerial decision making

Abstract: This paper documents a controlled experiment on the effect of adding a graphical model to a fictitious corporate security decision problem. The control group (N=44) saw a textual description, and the treatment group (N=41) was presented a graphical representation using the ArchiMate security extension modeling language in addition to the textual description. Besides the security investment decision, indicators of comprehension, risk perception, and decision confidence were measured as dependent variables. Sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…The last one contains empirical studies comparing graphical and textual representations for, e.g., business processes [36], software architectures [17], safety and system requirements [9, 42, 44ś46]. Recently, there were published a few empirical studies examining representations for security risks [15,19,25,50] or comparing graphical and tabular methods for security risk assessment in full scale application [22,24,27,30].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The last one contains empirical studies comparing graphical and textual representations for, e.g., business processes [36], software architectures [17], safety and system requirements [9, 42, 44ś46]. Recently, there were published a few empirical studies examining representations for security risks [15,19,25,50] or comparing graphical and tabular methods for security risk assessment in full scale application [22,24,27,30].…”
Section: Related Workmentioning
confidence: 99%
“…Yildiz and Böhme [50] recently conducted a controlled experiment with 85 participants to investigate the effects of risk visualization on managerial decision making in information security. This study showed that supplementing a textual description of security decision problem with graphical representation improves risk perception and participants' confidence in decisions, but does not contribute to the comprehension of the problem or security investment decision.…”
Section: Related Workmentioning
confidence: 99%